To Review on the Pharmacology of the Leaf Extract of Catharanthus Roseus - Parihar, Shweta; Sharma, Devender; Chirania, Amit; Telrandhe, Umesh B. (Asian Journal of Pharmaceutical Research and Development, 2022)
Catharanthus roseus a species, a well-known home-grown herb in India, that belong to the genus Catharanthus of the Apocynaceae family. The Catharanthus roseusroots, stems, flowers and leaves are employed in herbal therapy, and also used as a herbal plant and ornamental plant. It is native and endemic to Madagascar, although it is also planted as an ornamental and therapeutic plant in other parts of the world. Pharmacological and therapeutic research, on the leaf of the Catharanthus roseusand its active components are presented in this overview.